2011
DOI: 10.1016/j.bmcl.2011.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented C-2 arylation of indole with diazonium salts: Syntheses of 2,3-disubstituted indoles and their antimicrobial activity

Abstract: A novel reaction of indole with aryldiazonium salts leading to the formation of 2-aryl-3-(arylazo)indoles was discovered. The products were found to possess potent anti-MRSA and anti-LLVRE activities. The SAR studies indicate that the potentially metabolically labile azo functionality can be replaced with ether oxygen and thioether sulphur atoms without any loss of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Here, there remains an issue of regioselectivity when unsymmetric 1,4‐ketones are applied. Other reports of N−H‐carbazole synthesis are: b) the reaction of indole with two molecules of the same 1‐chloro‐4‐vinylbenzene under Pd/Cu catalysis followed by 6e‐cyclization affords 2,3‐bis(4‐chlorophenyl)‐9 H ‐carbazole in a 26 % combined yield; and c) the reaction of indole with 3‐methylpent‐1‐en‐4‐yn‐3‐ol catalyzed by a Ru complex produces 1,2‐dimethyl‐9 H ‐carbazole but in very low yield (15 %), and also with an issue of regioselectivity . In addition, Liang et al.…”
Section: Methodsmentioning
confidence: 99%
“…Here, there remains an issue of regioselectivity when unsymmetric 1,4‐ketones are applied. Other reports of N−H‐carbazole synthesis are: b) the reaction of indole with two molecules of the same 1‐chloro‐4‐vinylbenzene under Pd/Cu catalysis followed by 6e‐cyclization affords 2,3‐bis(4‐chlorophenyl)‐9 H ‐carbazole in a 26 % combined yield; and c) the reaction of indole with 3‐methylpent‐1‐en‐4‐yn‐3‐ol catalyzed by a Ru complex produces 1,2‐dimethyl‐9 H ‐carbazole but in very low yield (15 %), and also with an issue of regioselectivity . In addition, Liang et al.…”
Section: Methodsmentioning
confidence: 99%
“…3–6 Heterocyclic compounds having a fused aromatic ring containing a pyrrole are known as “indoles” 5. This class of heterocycles is very interesting as it has applications in the fields of biology, medicine, 714 and organic photovoltaics 15,16 and as fluorescent dyes 17. Indole derivatives are well-known for antiviral activity and current clinical studies are evaluating these types of compounds 14.…”
Section: Introductionmentioning
confidence: 99%
“…Our spectroscopic findings are further supported by our theoretical calculations. The detailed synthetic procedure of this molecule can be found in a previous publication 7. A detailed account of the photoactivated antibacterial activities of this compound will be published in a separate paper.…”
Section: Introductionmentioning
confidence: 99%
“…14 We showed that the metabolically labile azo group could be bioisosterically replaced by an ether or thioether functionalities leading to structures B , which were potent antibacterial agents as well. Unfortunately, these compounds were also found to inhibit the growth of human cervical cancer cells HeLa at comparable concentrations and this diminished our interest in pursuing them as novel antibacterials.…”
mentioning
confidence: 99%